Decoding BIM Challenges in Facility Management Areas: A Stakeholders’ Perspective - Paula Gordo-Gregorio; Hamidreza Alavi; Nuria Forcada (Buildings)
The adoption of building information modeling (BIM) in the operational and maintenance phase remains limited, with many buildings still managed through paper-based processes. While BIM has the potential to optimize various facility management (FM) areas—such as energy performance, security, administration, and space management—most studies only provide global analyses of adoption barriers. This study aims to identify and analyze area-specific barriers to BIM adoption in FM, highlighting the need for tailored integration strategies rather than a one-size-fits-all approach. By taking a novel approach, it investigates these barriers and demonstrates that BIM implementation cannot be uniformly applied across all FM areas. The methodology involves a multi-step process: first, a literature review is conducted to identify generic barriers to BIM implementation. Subsequently, FM areas are classified to provide a structured framework for analysis. Based on this classification, an interview structure is developed to gather expert insights on area-specific barriers. The research proposes that barriers should be assessed based on their impact. While contextual barriers or knowledge areas may be addressed through a global approach, ensuring BIM adoption across all areas requires consideration of specific characteristics. This approach will ultimately facilitate broader implementation in every domain.